PENERAPAN MODEL KARTU SHORTIR (CARD SORT) MELALUI PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR SEJARAH KELAS X MAN 1 TEMBILAHAN - Zulkifli Riswaldy; Isjoni Isjoni; Bedriati Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research is based on historical learning achievement of students X IPA 3 MAN 1 Tembilahan still have scores which stand under KKM that has been settled by the school that is 75. This research aims to improve learning process and students’ historical learning achievement by applying Card Sort through Problem Based Learning model. This research is a classroom action research with two cycles. The research instruments used are historical learning instruments and data collecting instruments. The historical learning instruments are Lesson Plans and Card Sort. The data collecting instruments are Observation Sheets and Students Historical Tests. Analysis techniques that used are descriptive narrative on qualitative data and descriptive statistics on quantitative data. Subject of this research are students of X IPA 3 MAN 1 Tembilahan in first semester of academic year 2018/2019, which consist of 11 males and 28 females with heterogeneous abilities. Based on the analysis of students and teacher activities after implementation of Card Sort through Problem Based Learning model, it can be concluded that there is an improvement of learning process. In Cycle I with percentage 69% and 82% in Cycle II. Based on the result, it can be concluded that the implementation of Card Sort through Problem Based Learning model can improve the learning process and the students’ historical learning outcomes at class X IPA 3 MAN 1 Tembilahan .Key Words: Historical Learning Achievement, Card Sort through Problem Based Learning Model, Classroom Action Research